Development of ATP13A2-deficient In vitro Model for PARK9 Parkinson’s Disease - Yap, Yiing J.; Chowdhury, Md Ezharul Hoque; Koh, Rhun Yian; Chye, Soi Moi; Leong Voon, Kenny Gah; Othman, Iekhsan; Ng, Khuen Yen (Current Signal Transduction Therapy, 2021)
Background: PARK9 familial Parkinson’s disease (PD) is caused by a loss-of-function mutation in the ATP13A2 gene in which the mutation impairs the autophagic-lysosomal degradation pathway and induces intraneuronal accumulation of alpha-synuclein. RNA interference has been a useful tool in generating in vitro knockdown model to study the physiological role of the gene. However, the availability of a validated ATP13A2-deficient in vitro model is limited. Objective: This study aimed to develop the ATP13A2-deficient PD model by delivering ATP13A2 siRNA into neuroblastoma cells using carbonate apatite nanoparticles (CA NPs). Method: CA NPs were fabricated using different concentrations of calcium chloride and characterised in the presence or absence of ATP13A2 siRNA. Time-dependent stabilities of CA NPs and CA NPs-associated siRNA (CA-siRNA) complex were evaluated by pH, turbidity, size, and zeta potential measurements. The dissolution abilities at acidic conditions of both complexes were investigated. Following that, green fluorescence protein (GFP) and four different siRNAs targeting ATP13A2 (siRNA_5, 6, 7, and 8) were transfected to cells with the fabricated CA NPs. Western blot was performed to determine the knockdown effect of the four siRNAs. Results: It was found that 4 mM calcium chloride was ideal for CA NP formation, while an incubation time of 48 hours was required to maintain the stability of nanoparticles. Successful transfection was confirmed by detection of fluorescence signal from the GFP plasmid and the subsequent silencing of this signal by transfecting GFP siRNA. Western blot analysis revealed that ATP13A2 protein expression was significantly reduced to 20% upon transfection with 20 nM of siRNA_5. Conclusion: ATP13A2-deficient PD model was successfully developed.
Keywords: ATP13A2